Risk factors for comorbid psychopathology in youth with psychogenic nonepileptic seizures. (May 2016) - Plioplys, Sigita; Doss, Julia; Siddarth, Prabha; Bursch, Brenda; Falcone, Tatiana; Forgey, Marcy; Hinman, Kyle; LaFrance, W. Curt; Laptook, Rebecca; Shaw, Richard J.; Weisbrot, Deborah M.; Willis, Matthew D.; et al.
Highlights: Youth with psychogenic seizures have different risks for psychopathology than siblings. Known risk factors for depression were not found in PNES youth. Lower IQ, anxiety sensitivity increased the likelihood of PTSD in PNES youth. Abstract: Purpose: To examine the risk factors for internalizing (anxiety, depression) and posttraumatic stress (PTSD) disorders, somatization, and anxiety sensitivity (AS) in youth with psychogenic non-epileptic seizures (PNES). Methods: 55 probands with PNES and 35 siblings, aged 8–18 years, underwent a psychiatric interview, cognitive and language testing, and completed somatization and AS questionnaires. Parents provided the subjects' medical, psychiatric, family, and adversity history information. Results: The risk factors for the probands' internalizing disorders (girls, older age of PNES onset), somatization (older age, epilepsy), and anxiety sensitivity (girls, adversities) differed from their siblings. The risk factors in the siblings, however, were similar to the general pediatric population. Proband depression was unrelated to the study's risk variables while PTSD was significantly associated with female gender and lower Full Scale IQ. Conclusions: Knowledge about the specificity of the risk factors for comorbid psychopathology in youth with PNES might facilitate their early identification and treatment.